Deterministic placement of ultra-bright near-infrared color centers in arrays of silicon carbide micropillars - Castelletto, Stefania; Al Atem, Abdul Salam; Inam, Faraz Ahmed; Bardeleben, Hans Jürgen von; Hameau, Sophie; Almutairi, Ahmed Fahad; Guillot, Gérard; Sato, Shin-ichiro; Boretti, Alberto; Bluet, Jean Marie (Beilstein Journal of Nanotechnology, 2019)
We report the enhancement of the optical emission between 850 and 1400 nm of an ensemble of silicon mono-vacancies (VSi), silicon and carbon divacancies (VCVSi), and nitrogen vacancies (NCVSi) in an n-type 4H-SiC array of micropillars. The micropillars have a length of ca. 4.5 μm and a diameter of ca. 740 nm, and were implanted with H+ ions to produce an ensemble of color centers at a depth of approximately 2 μm. The samples were in part annealed at different temperatures (750 and 900 °C) to selectively produce distinct color centers. For all these color centers we saw an enhancement of the photostable fluorescence emission of at least a factor of 6 using micro-photoluminescence systems. Using custom confocal microscopy setups, we characterized the emission of VSi measuring an enhancement by up to a factor of 20, and of NCVSi with an enhancement up to a factor of 7. The experimental results are supported by finite element method simulations. Our study provides the pathway for device design and fabrication with an integrated ultra-bright ensemble of VSi and NCVSi for in vivo imaging and sensing in the infrared.
Keywords: color centers; micropillars; proton irradiation; quantum sensing; silicon carbide; vacancy

(untitled) - Atatüre, M.; Englund, D.; Vamivakas, N.; Lee, S.-Y.; Wrachtrup, J. (Nat. Rev. Mater., 2018)

(untitled) - Weber, J. R.; Koehl, W. F.; Varley, J. B.; Janotti, A.; Buckley, B. B.; Van de Walle, C. G.; Awschalom, D. D. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Awschalom, D. D.; Hanson, R.; Wrachtrup, J.; Zhou, B. B. (Nat. Photonics, 2018)

(untitled) - Widmann, M.; Lee, S.-Y.; Rendler, T.; Son, N. T.; Fedder, H.; Paik, S.; Yang, L.-P.; Zhao, N.; Yang, S.; Booker, I.; Denisenko, A.; Jamali, M.; et al. (Nat. Mater., 2015)

(untitled) - Christle, D. J.; Falk, A. L.; Andrich, P.; Klimov, P. V.; Hassan, J. U.; Son, N. T.; Janzén, E.; Ohshima, T.; Awschalom, D. D. (Nat. Mater., 2015)

(untitled) - Christle, D. J.; Klimov, P. V.; de las Casas, C. F.; Szász, K.; Ivády, V.; Jokubavicius, V.; Ul Hassan, J.; Syväjärvi, M.; Koehl, W. F.; Ohshima, T.; Son, N. T.; Janzén, E.; et al. (Phys. Rev. X, 2017)

(untitled) - Castelletto, S.; Johnson, B. C.; Ivády, V.; Stavrias, N.; Umeda, T.; Gali, A.; Ohshima, T. (Nat. Mater., 2014)

(untitled) - Fuchs, F.; Stender, B.; Trupke, M.; Simin, D.; Pflaum, J.; Dyakonov, V.; Astakhov, G. V. (Nat. Commun., 2015)

(untitled) - Lohrmann, A.; Johnson, B. C.; McCallum, J. C.; Castelletto, S. (Rep. Prog. Phys., 2017)

(untitled) - Lienhard, B.; Schröder, T.; Mouradian, S.; Dolde, F.; Tran, T. T.; Aharonovich, I.; Englund, D. (Optica, 2016)

(untitled) - Kraus, H.; Soltamov, V. A.; Riedel, D.; Väth, S.; Fuchs, F.; Sperlich, A.; Baranov, P. G.; Dyakonov, V.; Astakhov, G. V. (Nat. Phys., 2014)

(untitled) - Wolfowicz, G.; Whiteley, S. J.; Awschalom, D. D. (Proc. Natl. Acad. Sci. U. S. A., 2018)

(untitled) - de las Casas, C. F.; Christle, D. J.; Ul Hassan, J.; Ohshima, T.; Son, N. T.; Awschalom, D. D. (Appl. Phys. Lett., 2017)

(untitled) - Lohrmann, A.; Iwamoto, N.; Bodrog, Z.; Castelletto, S.; Ohshima, T.; Karle, T. J.; Gali, A.; Prawer, S.; McCallum, J. C.; Johnson, B. C. (Nat. Commun., 2015)

(untitled) - Widmann, M.; Niethammer, M.; Makino, T.; Rendler, T.; Lasse, S.; Ohshima, T.; Ul Hassan, J.; Tien Son, N.; Lee, S.-Y.; Wrachtrup, J. (Appl. Phys. Lett., 2018)

(untitled) - Sato, S.-i.; Honda, T.; Makino, T.; Hijikata, Y.; Lee, S.-Y.; Ohshima, T. (ACS Photonics, 2018)

(untitled) - Yan, F.-F.; Wang, J.-F.; Li, Q.; Cheng, Z.-D.; Cui, J.-M.; Liu, W.-Z.; Xu, J.-S.; Li, C.-F.; Guo, G.-C. (Phys. Rev. Appl., 2018)

(untitled) - Bracher, D. O.; Hu, E. L. (Nano Lett., 2015)

(untitled) - Song, B.-S.; Yamada, S.; Asano, T.; Noda, S. (Opt. Express, 2011)

(untitled) - Kira, M.; Jahnke, F.; Koch, S. W. (Phys. Rev. Lett., 1999)

(untitled) - Zavoisky, E. J. (J. Phys. (Moscow), 1945)

Zero-Phonon Lines - Sild, O.; Haller, K. (Springer Berlin, 1988)

(untitled) - Debye, P. (Ann. Phys. (Berlin, Ger.), 1913)

(untitled) - Waller, I. (Z. Phys., 1923)

Principles of electron spin resonance - Atherton, N. M. (Ellis Horwood, 1993)

(untitled) - Delaney, P.; Greer, J. C.; Larsson, J. A. (Nano Lett., 2010)

(untitled) - Nagy, R.; Niethammer, M.; Widmann, M.; Chen, Y.-C.; Udvarhelyi, P.; Bonato, C.; Hassan, J. U.; Karhu, R.; Ivanov, I. G.; Son, N. T.; Maze, J. R.; Ohshima, T.; et al. (Nat. Commun., 2019)

(untitled) - Sörman, E.; Son, N. T.; Chen, W. M.; Kordina, O.; Hallin, C.; Janzén, E. (Phys. Rev. B, 2000)

(untitled) - Simin, D.; Soltamov, V. A.; Poshakinskiy, A. V.; Anisimov, A. N.; Babunts, R. A.; Tolmachev, D. O.; Mokhov, E. N.; Trupke, M.; Tarasenko, S. A.; Sperlich, A.; Baranov, P. G.; Dyakonov, V.; et al. (Phys. Rev. X, 2016)

(untitled) - Ivády, V.; Davidsson, J.; Son, N. T.; Ohshima, T.; Abrikosov, I. A.; Gali, A. (Phys. Rev. B, 2017)

(untitled) - Nagy, R.; Widmann, M.; Niethammer, M.; Dasari, D. B. R.; Gerhardt, I.; Soykal, Ö. O.; Radulaski, M.; Ohshima, T.; Vučković, J.; Son, N. T.; Ivanov, I. G.; Economou, S. E.; et al. (Phys. Rev. Appl., 2018)

(untitled) - Banks, H. B.; Soykal, Ö. O.; Myers-Ward, R. L.; Gaskill, D. K.; Reinecke, T. L.; Carter, S. G. (Phys. Rev. Appl., 2019)

(untitled) - Economou, S. E.; Dev, P. (Nanotechnology, 2016)

(untitled) - Koehl, W. F.; Buckley, B. B.; Heremans, F. J.; Calusine, G.; Awschalom, D. D. (Nature, 2011)

(untitled) - von Bardeleben, H. J.; Cantin, J. L.; Rauls, E.; Gerstmann, U. (Phys. Rev. B, 2015)

(untitled) - von Bardeleben, H. J.; Cantin, J. L.; Csóré, A.; Gali, A.; Rauls, E.; Gerstmann, U. (Phys. Rev. B, 2016)

(untitled) - Zargaleh, S. A.; Hameau, S.; Eble, B.; Margaillan, F.; von Bardeleben, H. J.; Cantin, J. L.; Gao, W. (Phys. Rev. B, 2018)

(untitled) - Zargaleh, S. A.; Eble, B.; Hameau, S.; Cantin, J.-L.; Legrand, L.; Bernard, M.; Margaillan, F.; Lauret, J.-S.; Roch, J.-F.; von Bardeleben, H. J.; Rauls, E.; Gerstmann, U.; et al. (Phys. Rev. B, 2016)

(untitled) - Zargaleh, S. A.; von Bardeleben, H. J.; Cantin, J. L.; Gerstmann, U.; Hameau, S.; Eblé, B.; Gao, W. (Phys. Rev. B, 2018)

(untitled) - Sato, S.-i.; Narahara, T.; Abe, Y.; Hijikata, Y.; Umeda, T.; Ohshima, T. (J. Appl. Phys., 2019)

(untitled) - Reithmaier, J. P.; Sęk, G.; Löffler, A.; Hofmann, C.; Kuhn, S.; Reitzenstein, S.; Keldysh, L. V.; Kulakovskii, V. D.; Reinecke, T. L.; Forchel, A. (Nature, 2004)

(untitled) - Ding, X.; He, Y.; Duan, Z.-C.; Gregersen, N.; Chen, M.-C.; Unsleber, S.; Maier, S.; Schneider, C.; Kamp, M.; Höfling, S.; Lu, C.-Y.; Pan, J.-W. (Phys. Rev. Lett., 2016)

(untitled) - Reitzenstein, S.; Forchel, A. (J. Phys. D: Appl. Phys., 2010)

(untitled) - Shin, C.; Jin, H.-H.; Kim, W.-J.; Park, J.-Y. (J. Am. Ceram. Soc., 2012)

(untitled) - Jang, Y.-S.; Zollfrank, C.; Jank, M.; Greil, P. (J. Am. Ceram. Soc., 2010)

(untitled) - Calusine, G.; Politi, A.; Awschalom, D. D. (Appl. Phys. Lett., 2014)

Conference on Lasers and Electro-Optics, OSA Technical Digest (Optical Society of America, 2019) - Lukin, D.; Dory, C.; Radulaski, M.; Sun, S.; Mishra, S. D.; Guidry, M.; Vercruysse, D.; Vučković, J. (4H-SiC-on-Insulator Platform for Quantum Photonics, San Jose, CA, U.S.A., 5.5.2019-10.5.2019, 2019)

(untitled) - Magyar, A. P.; Bracher, D.; Lee, J. C.; Aharonovich, I.; Hu, E. L. (Appl. Phys. Lett., 2014)

(untitled) - Lohrmann, A.; Karle, T. J.; Sewani, V. K.; Laucht, A.; Bosi, M.; Negri, M.; Castelletto, S.; Prawer, S.; McCallum, J. C.; Johnson, B. C. (ACS Photonics, 2017)

(untitled) - Radulaski, M.; Widmann, M.; Niethammer, M.; Zhang, J. L.; Lee, S.-Y.; Rendler, T.; Lagoudakis, K. G.; Son, N. T.; Janzén, E.; Ohshima, T.; Wrachtrup, J.; Vučković, J. (Nano Lett., 2017)

(untitled) - Kraus, H.; Soltamov, V. A.; Fuchs, F.; Simin, D.; Sperlich, A.; Baranov, P. G.; Astakhov, G. V.; Dyakonov, V. (Sci. Rep., 2014)

(untitled) - Simin, D.; Fuchs, F.; Kraus, H.; Sperlich, A.; Baranov, P. G.; Astakhov, G. V.; Dyakonov, V. (Phys. Rev. Appl., 2015)

(untitled) - Ohshima, T.; Satoh, T.; Kraus, H.; Astakhov, G. V.; Dyakonov, V.; Baranov, P. G. (J. Phys. D: Appl. Phys., 2018)

(untitled) - Degen, C. L.; Reinhard, F.; Cappellaro, P. (Rev. Mod. Phys., 2017)

(untitled) - Rühl, M.; Ott, C.; Götzinger, S.; Krieger, M.; Weber, H. B. (Appl. Phys. Lett., 2018)

(untitled) - Kraus, H.; Simin, D.; Kasper, C.; Suda, Y.; Kawabata, S.; Kada, W.; Honda, T.; Hijikata, Y.; Ohshima, T.; Dyakonov, V.; Astakhov, G. V. (Nano Lett., 2017)

(untitled) - Wang, J.; Zhou, Y.; Zhang, X.; Liu, F.; Li, Y.; Li, K.; Liu, Z.; Wang, G.; Gao, W. (Phys. Rev. Appl., 2017)

(untitled) - Hain, T. C.; Fuchs, F.; Soltamov, V. A.; Baranov, P. G.; Astakhov, G. V.; Hertel, T.; Dyakonov, V. (J. Appl. Phys., 2014)

(untitled) - Castelletto, S.; Almutairi, A. F. M.; Thalassinos, G.; Lohrmann, A.; Buividas, R.; Lau, D. W. M.; Reineck, P.; Juodkazis, S.; Ohshima, T.; Gibson, B. C.; Johnson, B. C. (Opt. Lett., 2017)

(untitled) - Akselrod, G. M.; Argyropoulos, C.; Hoang, T. B.; Ciracì, C.; Fang, C.; Huang, J.; Smith, D. R.; Mikkelsen, M. H. (Nat. Photonics, 2014)

(untitled) - Xu, Y.; Vučković, J. S.; Lee, R. K.; Painter, O. J.; Scherer, A.; Yariv, A. (J. Opt. Soc. Am. B, 1999)

(untitled) - Cochrane, C. J.; Blacksberg, J.; Anders, M. A.; Lenahan, P. M. (Sci. Rep., 2016)